(untitled) (Medico Legal Update, 2020)
Introduction: PCO is asignificant alteration in hormonal state that happen in females which lead to ovulatory reasonsof subfertility & amenorrhea in reproductive period. Polycystic Ovarian Syndrome was collecting of presenting symptoms and signs. If we had two of the following presenting sign and symptoms,we called this condition as PCO. 1. Oligomenorrhea & amenorrhea (menstrual and ovulating problem). 2. Signs of hyperandrogenimea (clinical or biochemical). 3. U/S features of polycystic ovaries which include (thick stoma on the periphery of the ovaries,which include multiple small follicles > 10and largest one < 9 mm,while the ovarian size > 10 cm3.Aims of the study :- analysis of Iraqi women in AL- Hilla city who present with problems in her menstrual cycle or fertility and assess their period of age when maximum symptoms and signs were appear,BMI, hereditary factors,occupation, residence, marital status and laboratory investigation to confirm our diagnosis (FSH, LH, AMH, PRLACTIN, TESTESTERONE) then vaginal u/s was done for married women and abdominal u/s done for unmarried one. Patients and Method: Case controlled study carried out for women that suffer from problems in her menstrual cycle and fertility from outpatient clinic in Babylon teaching hospital and some privet clinics, in period of 1year from(June 2017 to June 2018). 100 complaining women were participated in this study randomly after verbal and written consent which taken from them. Results: 100 women were shared in this study, we observed that percentage of infertility increase at the current time due to PCO for unknown reason, in addition to elevation percentage of PCOS frankly according to The Rotterdam criteria(symptoms and signs of presenting women), this multisystimic disorders disturb fertility to large extent because hormonal disturbances such as increase LHratio, Prolactin & AMH also increase ovarian volume due to thick stromal layer of the ovary then we assess affecting factors and relieving factors, its relation to patients age, BMI, occupation, residence and her hereditary state and hormonal analysis to document the diagnosis. Conclusions: Found fright increase of infertility in couples especially in our country in relative to the past, previously the incidence of infertility is about 12% of total couples and the incidence of PCO in general female about 35%(married or unmarred, may be due to delay discovery especially in unmarried group) & 45% in married women decreasing with progress of age.